2011
DOI: 10.1002/fld.2682
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional computation for flow‐induced vibrations in in‐line and cross‐flow directions of a circular cylinder

Abstract: SUMMARY We present numerical results for in‐line and cross‐flow vibrations of a circular cylinder, which is immersed in a uniform flow and is elastically supported by damper‐spring systems to compute vibrations of a rigid cylinder. In the case of a circular cylinder with a low Scruton number, it is well‐known that two types of self‐excited vibrations appear in the in‐line direction in the range of low reduced velocities. On the other hand, a cross‐flow vibration of the circular cylinder can be excited in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…However, in the case of Ur = 4.0, the wakes become non-symmetrical vortices behind the upstream vibrating cylinder. These results are the same as the wake shed from a vibrating circular cylinder (Kondo 2012). Figure 14 shows cross-flow vibration responses of the upstream circular cylinder and instantaneous vorticity contours of wakes shed from two circular cylinder during one period in the cross-flow vibration amplitudes of the upstream circular cylinder, when the reduced velocity Ur is 6.2.…”
Section: Flow-induced Vibrations Of Ansupporting
confidence: 60%
See 4 more Smart Citations
“…However, in the case of Ur = 4.0, the wakes become non-symmetrical vortices behind the upstream vibrating cylinder. These results are the same as the wake shed from a vibrating circular cylinder (Kondo 2012). Figure 14 shows cross-flow vibration responses of the upstream circular cylinder and instantaneous vorticity contours of wakes shed from two circular cylinder during one period in the cross-flow vibration amplitudes of the upstream circular cylinder, when the reduced velocity Ur is 6.2.…”
Section: Flow-induced Vibrations Of Ansupporting
confidence: 60%
“…Thus the resonance yields the large first-and second-excited vibrations in the in-line direction, as seen in Figure 7. As a result, we could catch the resonance phenomenon of the upstream circular cylinder for two tandem cylinders as well as a single circular cylinder (Kondo 2012). It is also observed that the f cd2 of the downstream stationary cylinder corresponds to the f cd1 of the upstream vibrating cylinder.…”
Section: Flow-induced Vibrations Of Anmentioning
confidence: 71%
See 3 more Smart Citations